Analisis Wacana Pesan Edukasi Pemilu pada Program “Warung Pengkolan” Episode 03 di TVRI Nasional - Didi Alzi Purnomo; Makroen Sanjaya (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Ahead of the election which will be held in February 2024, television is competing to broadcast various educational talk show programs, especially regarding elections or politics, one of which is TVRI Nasional. Ideally, people choose with their own thoughts and views. However, in reality there are still many people who choose randomly without logical reasons or just go along with it, even worse, they are indifferent to the election. The purpose of this research is to find out what educational messages are contained and how the educational messages contained in "Warung Pengkolan" Episode 03 are viewed from Teun Dijk's discourse analysis. This research uses a qualitative approach with the Van Dijk discourse analysis method, wanting to know messages according to macro structure, superstructure and micro structure. The results obtained are that the messages conveyed in the TVRI "Warung Pengkolan" program are contained in accordance with the macro structure, superstructure and micro structure. In the macro structure, it is to invite, educate and motivate young people or young Indonesian voters who this year have the right to exercise their right to vote and not the white group, because our choice really determines the future of the Indonesian nation. In the superstructure, it is divided into two perspectives, the first perspective is the correct way to choose, namely by looking at the vision and mission and the work program, the second perspective in choosing we have to carry out checks and balances and look at the track record, don't be trapped by the Echo Chamber phenomenon. In the micro structure of delivering education, a speaker or resource person must speak politely and politely and use language that is easy to understand. Because a speaker's words and behavior will determine whether the message can be conveyed clearly to the audience.